2014
DOI: 10.5713/ajas.2013.13774
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Behaviour in Grouped Pigs Fed Fibrous Diet

Abstract: The objective of the study was to investigate the effect of feeding fibrous diets on growth performance and occurrence of aggressive behaviours in growing pigs. Sixty healthy castrated pigs (initial body weight: 46.7±4.35 kg) were used. A basal diet was diluted with maize cobs to two levels (0 and 160 g/kg dry matter). Behavioural activities were observed using video cameras for three weeks, 8 h/d starting at 0800 h. Pigs subjected to control diet gained more weight compared to pigs receiving fibrous diet in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…Similarly, De Jong et al [56] studied physiological effects of using straw bedding and found that pigs in enriched environments had higher cortisol concentrations than pigs in barren environments. Bakare et al [67] and Pambu Gollah et al [68] reported that corticosteroid hormones bind two types of receptors in the brain called glucocorticoid receptors and mineralocorticoid receptors. These receptors give pigs the ability to respond adaptively to their environment whether barren or enriched depending on the balance between these receptors.…”
Section: Improving Pig Productivity Through Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, De Jong et al [56] studied physiological effects of using straw bedding and found that pigs in enriched environments had higher cortisol concentrations than pigs in barren environments. Bakare et al [67] and Pambu Gollah et al [68] reported that corticosteroid hormones bind two types of receptors in the brain called glucocorticoid receptors and mineralocorticoid receptors. These receptors give pigs the ability to respond adaptively to their environment whether barren or enriched depending on the balance between these receptors.…”
Section: Improving Pig Productivity Through Enrichmentmentioning
confidence: 99%
“…Intermediary blood metabolites interact with the central nervous system to regulate different behavioral patterns of pigs Bakare et al [67]. Blood metabolites can also give an indication of the animal’s nutritional status [62].…”
Section: Improving Pig Productivity Through Enrichmentmentioning
confidence: 99%
“…También existe la posibilidad de que con un 15 % de harina de este follaje en la ración, alguna de sus propiedades químico-físicas estaría ejerciendo una influencia negativa en el consumo voluntario, lo que parece ser característico que ocurra en cerdos (Bakare et al, 2013(Bakare et al, , 2014Kanengoni et al, 2015), debido a la importancia de la fracción fibrosa en los recursos alimentarios arbóreos.…”
Section: Acceptabilityunclassified
“…Furthermore, probably with 15 % of gliricidia foliage meal in the ration, some of its physicochemical properties should be exerting a negative influence on the voluntary feed intake, which appears to be characteristic to occur in pigs (Bakare et al, 2013(Bakare et al, , 2014Kanengoni et al, 2015), due to the importance of the fibrous fraction in arboreal alimentary resources.…”
Section: Patrón De Consumomentioning
confidence: 99%
“…De Leeuw et al (2008) reported that pigs fed on fibrous diets showed longer satiety or less feeding motivation due to gut fill. On the other hand, a study by Bakare et al (2014) revealed that pigs spent more eating time on fibrous diet like maize cobs compared to concentrate diet formulated from different proportion of yellow maize, soya bean, soya bean cake, wheat bran, sunflower, sunflower oil cakes. They emphasized that the longer eating time recorded on maize cobs is due to unsatisfied feeding motivation of the pigs to meet their nutrient requirement.…”
Section: Digestibilitymentioning
confidence: 99%